2021
DOI: 10.1007/s00592-021-01681-2
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-glucose cotransporter 2 inhibition prevents renal fibrosis in cyclosporine nephropathy

Abstract: Aims Sodium-glucose cotransporter 2 (SGLT2) inhibitors, a new class of antidiabetic drugs, are nephroprotective in case of diabetes, but whether a similar beneficial effect may be detectable also in case of chronic non-diabetic kidney diseases remains still unknown. The aim of this study was to evaluate the effects of empagliflozin, a SGLT-2 inhibitor, on the progression of cyclosporine nephropathy, in the absence of diabetes. Methods Sprague Dawley rats (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 48 publications
5
26
0
Order By: Relevance
“…As seen in other rodent studies (Kapoor et al, 2015;Rajasekeran et al, 2018;Castoldi et al, 2020;Yamato et al, 2020;Castoldi et al, 2021), SGLT2 inhibition caused significant or at least a strong trend towards renal hypertrophy in our animal models under hyperfiltrating conditions, but also in healthy kidneys. Whether the weight gain of the kidney is due to expansion of cell volume or edema formation and which parts of the nephron experience cell growth cannot be answered at this point and requires further investigation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As seen in other rodent studies (Kapoor et al, 2015;Rajasekeran et al, 2018;Castoldi et al, 2020;Yamato et al, 2020;Castoldi et al, 2021), SGLT2 inhibition caused significant or at least a strong trend towards renal hypertrophy in our animal models under hyperfiltrating conditions, but also in healthy kidneys. Whether the weight gain of the kidney is due to expansion of cell volume or edema formation and which parts of the nephron experience cell growth cannot be answered at this point and requires further investigation.…”
Section: Discussionsupporting
confidence: 88%
“…A number of in vivo studies reported no improvement of renal impairment by SGLT2 inhibitors caused by, e.g., 5/6 nephrectomy in rats (Zhang et al, 2016;Rajasekeran et al, 2018), polycystic kidney disease in rats (Kapoor et al, 2015), oxalate-induced nephrocalcinosis in mice (Ma et al, 2017) and adenine-induced fibrosis in rats (Yamazaki et al, 2020). On the contrary, data supporting a renal benefit by SGLT2 inhibition were provided from disease models like ischemia-reperfusion injury (Chang et al, 2016), unilateral ureteric obstruction (Abbas et al, 2018), proteinoverload proteinuria (Cassis et al, 2018), Ang II-dependent hypertension (Castoldi et al, 2020), cyclosporine-A nephropathy (Castoldi et al, 2021), adenine nephropathy (Yamato et al, 2020) and salt-sensitive hypertension in uninephrectomized rats (Kim et al, 2019). It is worth mentioning that the discrepant results in the aforementioned studies are not due to the different SGLT2 inhibitors used, as both positive and negative results were reported for most of the compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Castoldi et al which examined the effects of empagliflozin on the progression of cyclosporine-A (CsA) nephropathy, in the absence of DM, showed that empagliflozin can reduce the CsA-induced glomerular and tubulo-interstitial fibrosis and renal inflammation. 23 Thus the role of SGLT2i may be even more important given the fact that cyclosporine toxicity is of concern in renal transplant patients. SGLT2 inhibition also reduce tubular workload and hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…The count of monocyte/macrophage and T-lymphocytes infiltration was performed on formalin fixed and paraffin embedded transmural myocardial sections (3 µm), using respectively a monoclonal mouse anti-rat monocytes/macrophage antibody (CD68, clone ED1, MAB 1435, Chemicon, Temecula, CA, USA) as previously described [38], and a rabbit monoclonal anti-rat T-lymphocyte antibody (CD3 [SP7] ab16669, Abcam, Cambridge, UK). For each antibody, the histological sections were deparaffinized and rehydrated, treated by boiling in citrate buffer (0.01 mol/L, Ph 6) in microwave (750 W), and incubated over night at 4 • C with anti-CD68 or anti-CD3 antibody (dilution 1:300 for both antibodies).…”
Section: Immunohistochemical Evaluation Of Myocardial Monocyte/macrop...mentioning
confidence: 99%
“…Two independent pathologists blinded to the treatment counted respectively CD68 and CD3 positive cells and took the average. The macrophages and the T-lymphocytes were expressed as mean value of positive cells/fields [38].…”
Section: Immunohistochemical Evaluation Of Myocardial Monocyte/macrop...mentioning
confidence: 99%